Does Disclosure of Governance Accountability and Digitalization Business Processes Through The Company Website Strengthen The Value Relevance of Financial Information? - Henry Wahyu Indrianto; I Made Narsa (Universitas Muhammadiyah Malang, 2025)
Purpose: This research aims to test whether Governance Accountability Disclosure (GAD) and Digital Business Process Disclosure (DBPD), made available through corporate websites, reinforces the value relevance of financial information. Methodology/approach: This research uses cross-sectional data from 2023 annual reports and website content analysis from 84 companies that have automated and consumer-facing digital service business activities. Quantitative analysis was processed using multiple linear regression. Findings: The findings of this study found that GAD has no influence on the relevance of financial value. In contrast, DBPD has a significant influence on financial value relevance. This result indicates that DBPD information increases value relevance for investors, because the information in it reinforces the importance of financial information more than the information in GAD. The test results by interacting GAD and DBPD with earnings per share show that only GAD has an influence on the value relevance of financial information, although not significant. Practical implications: This research provides strategies to enhance company value that can be achieved by empowering governance systems and strengthening the capacity of digitized businesses, and then disseminating information through digital means. Originality/value: Company websites have economic potential, but extensive analysis is lacking even though companies are increasingly interested in fostering a climate of trust through online disclosure, especially when interacted with the digitization of business process information, transparent corporate governance policies, and financial position. This empirical research makes a unique contribution by adding to the literature on information technology in accounting, which is linked to agency theory and signaling theory